ESTUDO DA ESTABILIZAÇÃO MECÂNICA DE SOLO RESIDUAL DE IJUÍ /RS – EFEITOS NA PERMEABILIDADE E RESISTÊNCIA - Pinheiro, Rinaldo; Specht, Luciano P.; Mensch, Natália G.; Kelm, Tamile A.; Lima, Geannina T. d. S. (Salão do Conhecimento, 2013)
Resumo